Deposition of economic cocatalysts on graphitic carbon nitride for efficient photocatalytic hydrogen generation - Yin, Lisha (2015)
Energy crisis and environmental issues are two most severe problems faced by all human beings on this planet. In order to solve the two problems, researchers are seeking for alternative energies other than fossil fuels. The alternative energies should be abundant, clean as well as sustainable. From this point of view, hydrogen is a good candidate. Hydrogen could be generated from a clean process, photocatalytic water splitting, in which semiconductor photocatalyst is a key factor. Polymeric graphitic carbon nitride (g-C3N4), which could respond to visible light with a proper band gap of 2.7 eV and suitable conduction band (CB) of -1.1 eV to reduce protons, is demonstrated to be able to achieve photocatalytic H2 generation. However, pristine g-C3N4 exhibits a poor performance for photocatalytic H2 generation due to the fast recombination of photoexcited electrons and holes. Whereas loading of noble metal cocatalysts such as Pt could enhance the performance. This project aims at suppressing the charge carrier recombination and thus enhancing the photocatalytic activity of g-C3N4 by depositing earth abundant and low-cost cocatalysts, e.g. bimetallic alloy, PtCo, and noble metal free NiS2. Firstly, the noble metal Pt cocatalyst was partially replaced with Co and a series of PtCo alloys with different compositions were loaded on to the surface of g-C3N4 via the solvothermal method. Different amounts of Pt and Co precursors were added to adjust the compositions and the H2 evolution results indicated the highest activity was obtained at an atomic ratio of 2.5 to 1(Pt to Co). This Pt2.5Co/ g-C3N4 with 1wt% cocatalyst loading exhibited an even higher activity than that of Pt (1 wt%) loaded g-C3N4 prepared under same conditions. The constant H2 evolution rate of 1wt% Pt2.5Co/ g-C3N4 under continuous 25-hour illumination under visible light suggested this alloy is highly stable on g-C3N4. The photoluminescence spectra and photoelectrochemical properties measurements imply that PtCo alloy could efficiently inhibit the recombination of photogenerated electrons and holes and therefore enhance the photocatalytic H2 production activity of g-C3N4. Secondly, the noble metal Pt cocatalyst was fully replaced with earth abundant and noble metal free cocatalyst, NiS2. NiS2/g-C3N4 composite with different weight percentages were synthesized via the hydrothermal method using thiourea and nickel acetate tetrahydrate as precursors. The presence of NiS2 was confirmed by X-ray diffraction pattern (XRD), transmission electron microscope (TEM) and X-ray photoelectron spectra (XPS). The H2 evolution test indicates that NiS2 loading could increase activity of g-C3N4 dramatically and 2 wt% loading of NiS2 on g-C3N4 shows the best performance, even better than 1 wt% Pt/g-C3N4 from photodeposition. Photoluminescence (PL) spectra of the samples suggest that the enhancement is associated with the more effective charge carrier separation as well. In summary, this thesis is devoted to developing earth abundant, low-cost, stable and more importantly, effective g-C3N4 based composites for photocatalytic H2 evolution. Studies on PtCo/g-C3N4 and NiS2/g-C3N4 reveal PtCo alloy and NiS2 as cocatalysts are effective in suppressing the charge carrier recombination to enhance the photocatalytic activities as well as reducing the cost on photocatalyst systems. Therefore, this thesis demonstrates PtCo alloy and NiS2 are excellent and promising cocatalyst candidates.